In vitro study of anti microbial activity of fermented coconut water extracted with different solvents against bacterial leaf blight of rice / Nur Atiqah Amiza Mohd Taufik - Mohd Taufik, Nur Atiqah Amiza (Faculty of Plantation and Agrotechnology, 2018)
Bacteria leaf blight caused by Xanthomonas oryzae is among devastating bacterial disease of rice. Control management of the disease using chemical caused a lot of problem including lead to resistant of the microorganism. Alternative solution of to the problem is controlling the disease using biological approach. One of biological control is the beneficial microorganism. Beneficial microorganism can be found everywhere including in coconut water. Addition of essential nutrient from molasses to mature coconut water would help the beneficial microorganisms can produce antimicrobial compound that have ability to control X. oryzae, that causal agent by BLB. Hence, the objective of the study are to screening the potential of antimicrobial activity from fermented mature coconut water extracted with different solvent against X. oryzae in vitro, and to determine the minimal inhibition concentration (MIC) and minimal bactericidal concentration (MBC) of fermented mature coconut water against X. oryzae. The antimicrobial activities were evaluated by measuring the diameter of inhibition zone diameter by using well diffusion method. The highest inhibition zone diameter is positive control that is using methanol extract with (2.2 cm). The inhibition started to happened by using methanol extract and followed by aqueous extract (1.5 cm). Negative control of each extract showed no activity of inhibiton zone, and positive control (Streptomycin sulphate) showed the activity of inhibition zone. Methanol extract was chosen for Minimal inhibitory concentration and Minimal bactericidal concentration as this extract perform highest inhibition zone. The minimum inhibitory of fermented mature coconut water extracted with different solvent by using the different concentration were determined by using serial broth dilution method. The result MIC showed of the 10% of concentration can against the X. oryzae. While the result MBC showed the 20% of concentration can inhibit kill the pathogens.